Pengaruh Literacy Financial, Experienced Regret, dan Overconfidence Terhadap Pengambilan Keputusan Investasi Di Pasar Modal - Iskandar Budiman; Zefri Maulana; Safwan Kamal (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to determine the effect of financial literacy, experienced regret, and overconfidence on investment decision making in the capital market. Method of this study was a quantitative approach. This study used nonprobability sampling and determined the number of samples from a population using quota sampling based on certain criteria in accordance with research conducted by researchers. The determined sample was 45 respondents. Respondents criteria were all investors who actively transact at least one day several times a transaction and a maximum of once a month transactions and investors who have experienced adverse events in stock investments such as losses but are still actively transacting. This study used a Likert scale measurement. The results of this study was based on a partial test showing that financial literacy did not affect investment decision making in the capital market, while experienced regret, and overconfidence affect investment decision making in the capital market. The conclusion of this study was based on the analysis of the coefficient of determination (adjusted R2) that 47.3% of the variation in the value of investment decision making in the capital market at IAIN Langsa Investment Gallery was determined by three influential variables, namely financial literacy, experienced regret, and over-confidence. While the remaining 52.7% was explained by other variables not included in the equation above.